Determinants of Banking Performance for Commercial Banks on Indonesia Stock Exchange - Elgi, Afrizal; Karnasi, Reniati (Dinasti Publisher, 2024)
This study examines the determinants of Indonesian banking performance caused by global uncertainty such as geopolitical conflicts and post-pandemic conditions. The study adopted quantitative approach and used samples by 34 commercial banks listed on Indonesia Exchange Stock period 2017 to 2023. Panel data regression used as analytical method. This study used bank size, bank capital, liquidity, credit risk, and inflation rate as independent variables. Furthermore, bank performance was measured by return on asset. The findings of this study were bank size and inflation rate positively impact on return on asset while the other variables have no relationship on bank performance. This study could be used as reference for future research and for banking management decision-making.